Application of Semistructured Interview Based on Doctor-Patient Perspective in Constructing a Palliative Care Regimen for Patients with Advanced Heart Failure - Ting Zhou; HaiQin Cai; ChunHui Xu (Emergency Medicine International, 2022)
Objective. The aim of this study is to explore the application of semistructured interview based on doctor-patient perspective in constructing a palliative care regimen for patients with advanced heart failure. Methods. 112 patients with advanced heart failure who were admitted to the hospital were selected between December 2019 and December 2020, and they were randomly divided into an interview group and a routine group, with 56 cases in each group. The routine group was given routine nursing for advanced heart failure while the interview group developed a palliative care regimen based on a semistructured interview from the doctor-patient perspective. The psychological states (Depression-Anxiety-Stress Scale (DASS-21)), symptoms (Memorial Symptom Assessment Scale-Heart Failure (MSAS-HF)), quality of life (Kansas City Cardiomyopathy Questionnaire (KCCQ)), and prognosis (readmission rate, mortality rate) were compared between the two groups before and after intervention. Results. Compared with before intervention, there were no significant differences in the scores of DASS-21, MSAS-HF, and KCCQ in the routine group after intervention (P>0.05), and the scores of DASS-21 and MSAS-HF in the interview group were decreased while KCCQ scores were increased (P<0.05). Scores of DASS-21 and MSAS-HF and readmission rate were lower while the KCCQ scores were higher in the interview group compared with those in the routine group (P<0.05). There was no significant difference in the mortality rate between the two groups (P>0.05). Conclusion. The application of a semistructured interview based on the doctor-patient perspective to construct the palliative care regimen for patients with advanced heart failure can eliminate the negative emotions, improve the psychological states, relieve the clinical symptoms, enhance the quality of life, and reduce the risk of readmission.